Erosion or extension of res inter alios acta with regard to the linked contracts real estate - Mendoza del Maestro, Gilberto (2018)
In the present work an analysis of the linked contracts phenomenon has been carried out from the beginning for its understanding between the intensity of the link, so that it becomes evident in the current economic situation and one should stop seeing the contracts as only entities isolated.